Gambaran Kinerja Perawat dalam Pendokumentasian Askep di Rawat Inap Rumah Sakit Indriati Solo Baru - Anggita Yuliana Nugraheni; Atiek Murharyati; Setiyawan (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2024)
The performance of nurses is a crucial indicator in achieving health service goals, including the stages of assessment, diagnosis, intervention, implementation, and evaluation. The study aimed to describe the nurse's performance in documenting nursing care in the inpatient room of Indriati Solo Baru Hospital. The investigation employed a quantitative approach, with a sample of 18 nurses selected through the total sampling method. Data were collected utilizing a questionnaire and analyzed using the univariate method. The findings indicated that the overall performance of nurses in nursing care documentation within the Sakura inpatient room of Indriati Solo Baru Hospital was rated as good, achieving a score of 72.2%. An age analysis revealed that most nurses were aged between 20 and 30 years (88.9. Furthermore, all respondents werfe female (100%). Regarding educational qualifications, a significant proportion of the nurses held a Ners degree (66.7%). Regarding their professional experience, most nurses in the Sakura room had over one year of work experience (77.8%). The assessment results indicate a classification of